Touchless InteractionUsing Magnetometer for Mobile Games - Jason Wihardja; Raymond Kosala (Bina Nusantara University, 2016)
This paper proposes an alternative method for conducting touchless interaction. Using a magnetometer sensor, we attempt to map some common gestures into something that can be understood by a magnetometer sensor. To demonstrate the concept, an application and a punching game that utilize this principlewere developed. Using the application, usersareable to perform a common swiping gesture using a magnetometer sensor. When the gamedetects a punch gesture, it will respond accordingly. The application was tested and compared against an existing touchless interaction technology. The test results showed that there are some aspects where the magnetometer solution is better compared to the existing solution. This suggests that touchless interaction using magnetometersmight have a promising future.